Effectiveness of e-Learning during the COVID-19 Pandemic among the Undergraduate Medical Students in Nepal: An Online Survey - Adhikari, Purushottam; Paudel, Sumedha; Pandey, Rajan Raj; Parajuli, Abhigya; Pyakuryal, Abhishree (Journal of Pharmacy Practice and Community Medicine)
Introduction: The COVID-19 pandemic has shifted the medical education to the virtual mode in most of the countries. Though online learning has been practiced for long and proved to be effective, its usefulness should be looked for in developing countries like Nepal. Methods: An online survey was conducted among undergraduate medical students with the help of a structured self-administered questionnaire consisting of demographic information, modalities of online classes they are taking and their opinion regarding the online classes. Results: Most of the students had access to the devices and internet facilities though some of the students responded that they have no internet facility at home. More than half of the students have answered that they are having some sort of visual problem after the online classes have started. Most of the students responded that the internet connectivity issue is a hindrance to online learning. More than half of the students strongly disagree that online class should be continued even after the pandemic is over. Conclusion: There are lots of obstacles in virtual learning in resource-limited countries like ours. The effectiveness of e-learning should be evaluated among the students and the shortcomings of virtual learning should be addressed by concerned authorities.
Keywords: e-learning; COVID-19 pandemic; Medical education; Online class; Medical school